SUREWASTE: REVOLUSI BERKELANJUTAN DALAM PENGOLAHAN AIR LIMBAH BERBASIS INTERNET OF THINGS (IOT): Surewaste: Revolusi Berkelanjutan Dalam Pengolahan Air Limbah Berasis Internet Of Things (IOT) - Pandu Wicaksono; Fiadita Maharani; Ida I Dewa Agung Ayu Prabawanti; Athaya Oktavianisa; Darmawan, Very (Jurnal Teknik Sumber Daya Air, 2025)
SUREWASTE (Sustainable Revolutionizing Wastewater Treatment) is an innovation designed to solve the flooding and clean water crisis in the Sepaku Sub-district, Penajam Paser Utara District, East Kalimantan, Indonesia. The area suffers from frequent flooding due to land use change, sub-optimal drainage systems, and river siltation, while the clean water crisis is further exacerbated by water deficit. The SUREWASTE concept is based on Smart Water Management using the Internet of Things (IoT). The main focus includes handling rainwater runoff with porous asphalt and eco drainage, as well as water treatment into raw water and drinking water through retarding basins. Rubberized asphalt and eco drainage systems were implemented with the help of IoT to monitor and control water levels. Water treatment involves organic filters and reverse osmosis, customized according to water conditions. Water quality monitoring is done with various sensors such as pH, biosensor, DO, BOD, TSS, MQ-135, and COD, with results evaluated using the Department of Environment Water Quality Index (DOE WQI). An Arduino-based automatic water machine control, controlled via smartphone, was used to regulate water flow. The raw water and drinking water tanks are equipped with HC-SR04 sensors to detect the water level. The water distribution process involves WhatsApp bot and web monitoring. The method used in this scientific work is the descriptive qualitative and quantitative analysis method so that from the results of the data processing carried out, the implementation of SUREWASTE is expected to overcome flooding and provide clean water sources through the processing of alternative water resources in Sepaku District, in line with the Sponge City concept and the Sustainable Development Goals (SDGs), especially the sixth point regarding sustainable management of clean water and sanitation for all.